Proporsi Tepung Terigu,Tepung Tempe Dan Tepung Biji Nangka Terhadap Kandungan Mutu Kimia Biskuit Sebagai Makanan Tambahan Untuk Balita - Yuliana Salman; Eka Febriani (Jurnal Kesehatan Indonesia, 2017)
The nutritional problem is essentially a public health problem, but its mitigation can not be done with medical approach and health service only, so the cause of nutritional problem is multifactor. In national, the prevalence of less body weight and less nutrition in 2010 decreased to 17.9% in 2013 increased to 19.6%. Biscuits is a type of product that is considered able to meet the requirements to improve the nutritional status of biscuits because it is one of the foods favored by the wider community with the use and addition of food ingredients such as tempe and jackfruit seeds that have a fairly good nutritional content. The type of this research is experimental. The research design is Randomized Complete Design (RAL), with 4 treatments and 3 replication. The results showed that treatment of P3 contained the highest protein, carbohydrate and calcium content of 12.7%, 71.87%, 97.67% with proportion (50% flour: tempe 30% flour: 20% jackfruit flour) and the lowest yield is in treatment P0 with proportion (100% flour: 0% tempe flour: 0% jackfruit flour). Based on the results of this study it can be concluded that the addition of flour seeds and jackfruit seed flour can affect the levels of protein, carbohydrate and calcium